Ciudadanía y juventud : constitución de los jóvenes en sujetos ciudadanos (2002)
ABSTRACT: The present article studies the relationship between the notions of youth and citizenry. These concepts are conceived of as historical products that may disappear according to economic, political and territorial circumstances that make up their environment. Special attention is paid to the way in which current economic logic and dominant policies are eroding the environment that make the notion of youth possible, both in developed and developing countries. Youth is regarded as a modern cultural asset which made possible not only to prepare for work but also to think and set a critical distance from one’s own culture. For its constitution and defense, the author suggests coordinating the concept of policy of difference. This concept not only helps to link youth to the process of the public policies, but also to build a platform, acting from which young people can participate in the political arena and become citizens by themselves.